2016
DOI: 10.5334/gjgl.24
|View full text |Cite
|
Sign up to set email alerts
|

Unacceptable but comprehensible: the facilitation effect of resumptive pronouns

Abstract: It is often assumed in the theoretical syntax literature that intrusive resumptive pronouns can rescue island violations. However, recent experimental investigations did not provide strong evidence for such a rescuing effect. The current study examines intrusive resumption in Italian and English. In four experiments, we show that resumption indeed improves island violation to some degree, but such an effect is sensitive to task and contextual manipulations. In particular, the rescuing effect only surfaces with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 26 publications
2
49
1
Order By: Relevance
“…This interpretation echoes recent studies which suggest offline acceptability judgments correlate with processing efforts required from comprehenders to obtain a specific sentence interpretation (Hofmeister and Sag, 2010;Hofmeister et al, 2013). On the Accessibility Theory proposed by Ariel (1991Ariel ( , 2001), more informative, unambiguous, and unattenuated expressions encode lower accessibility, which is translatable into greater comprehensibility, leading to greater acceptability (Beltrama and Xiang, 2016;Burmester et al, 2014;Engelhardt et al, 2006;Hofmeister et al, 2013). In other words, the more obscure the meaning is and therefore more effort is needed from comprehenders to search for a specific meaning, the less acceptable it is perceived Linguistic & individual factors in meaning comprehension Figure 6: Self-paced reading results: Interval x VerbType interaction in the High-AQ vs. Low-AQ group (Lai and Piñango, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…This interpretation echoes recent studies which suggest offline acceptability judgments correlate with processing efforts required from comprehenders to obtain a specific sentence interpretation (Hofmeister and Sag, 2010;Hofmeister et al, 2013). On the Accessibility Theory proposed by Ariel (1991Ariel ( , 2001), more informative, unambiguous, and unattenuated expressions encode lower accessibility, which is translatable into greater comprehensibility, leading to greater acceptability (Beltrama and Xiang, 2016;Burmester et al, 2014;Engelhardt et al, 2006;Hofmeister et al, 2013). In other words, the more obscure the meaning is and therefore more effort is needed from comprehenders to search for a specific meaning, the less acceptable it is perceived Linguistic & individual factors in meaning comprehension Figure 6: Self-paced reading results: Interval x VerbType interaction in the High-AQ vs. Low-AQ group (Lai and Piñango, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…For this reason, our results for Basque can be said to make manifest the activation of a repair strategy (Frazier and Clifton, 2011; Phillips et al, 2011; Gibson et al, 2013; Beltrama and Xiang, 2016, and others) and a structural/syntactic priming (Ivanova et al, 2012) that turns a syntactically ungrammatical sentence into a well-formed input where the NDE (a non-negative polarity item in this case) appears to be licensed despite the absence of any overt c-commanding licensor in the syntactic structure (Vasishth et al, 2008). In grammatical terms, in the absence of an overt negative marker ez , a null operator NEG, as a last resort option (Zeijlstra, 2004), might be postulated at the syntactic representation of these sentences in order to account for the 31.5% of items that are still considered acceptable but are given a SN reading 83.96% of the time on average (see Table 2 in Appendix 3).…”
Section: Discussionmentioning
confidence: 65%
“…In fact, several psycholinguistic studies have shown that comprehenders are able to report an initial perception of acceptability and recover an interpretation from ungrammatical sequences (e.g., the amelioration of wh-island violations, Atkinson et al, 2016; the processing facilitation of ungrammatical sequences that contain resumptive pronouns, Beltrama and Xiang, 2016; and the acceptability of semantically implausible sequences that are perceived as plausible sentences, Gibson et al, 2013). Other studies have concentrated on how comprehenders can achieve an interpretation of ungrammatical or ill-formed sentences by covertly correcting the sentence into a well-formed input according to certain principles of repair (Frazier and Clifton, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, an RP can, by overtly expressing the tail of a wh-dependency, relieve some of the cognitive load on the speaker's limited resources in situations where incremental production (or potentially comprehension) would benefit from an overt link to the position that triggered the dependency search (Ferreira & Swets 2005). This argument has typically been made in reference to RPs located in positions that grammatically permit a gap, but such a mechanism may also be consistent with a limited local comprehension mechanism (Beltrama & Xiang 2016;Asudeh, 2004).…”
Section: Resumptive Pronounsmentioning
confidence: 99%